Development and Challenges in Front of Clusters in Bulgaria - Georgieva, Slavka (Vilnius University Open Series, 2021)
The importance of clusters for economic development, competitiveness and innovation is growing, and the diverse nature of cluster initiatives is becoming a popular approach to their creation, validation and development in sectors where both resources and opportunities are available. The elaboration presents the development of the clusters and their role for the modern Bulgarian economy, the conducted national policy in the sphere, the applied instruments in the context of the EU policy. The aim is to present the development of clusters in Bulgaria, highlighting the specificity of the implemented cluster initiatives and defining some challenges for their future development. Increasing competitiveness through cluster development is seen as a key strategic tool for achieving socio-economic development. It is emphasised that the success of cluster initiatives depends on companies and Bulgarian producers, striving through joint efforts to achieve higher competitiveness.